ANALISIS PEMAHAMAN KONSEP MATEMATIKA BERDASARKAN GENDER DAN TINGKAT KEMAMPUAN SISWA PADA MATERI POLINOMIAL - Sandra, Nabila Novia; Sari, Raras Kartika (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study aims to analyze students’ understanding of mathematical concepts based on gender and ability levels in the topic of polynomials at SMAN 14 Bandar Lampung. The study employed a descriptive qualitative approach involving six eleventh-grade students selected through purposive sampling to represent both male and female students with high, medium, and low levels of achievement. Data were collected through observation, tests, and interviews, and analyzed in three stages: data reduction, data presentation, and conclusion drawing. The results showed that high-ability male students were able to fully meet all three indicators of conceptual understanding translation, interpolation, and extrapolation. High-ability female students met only the translation and interpolation indicators, while medium-ability male students met all three indicators. In contrast, medium-ability female students were unable to fulfill any of the indicators due to difficulties in interpreting and applying concepts. Low-ability students, both male and female, were unable to fully meet any of the indicators. Gender was found to influence conceptual understanding, with male students performing better than female students. In conclusion, differences in gender and ability levels affect students’ understanding of mathematical concepts. Therefore, learning strategies that consider individual characteristics are essential to enhance the effectiveness and meaningfulness of mathematics learning.